Familie, musik og taknemlighed - Chaim Goldschmidt, Henrik (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
The Goldschmidt family has its roots in Breslau, a German town that became part of Poland after World War I. Here Helmuth Goldschmidt, my grandfather, was born in 1902. He was the youngest of four siblings, all of whom miraculously survived the Holocaust. The article tells the story of how they survived. The oldest brother was arrested and placed in a French camp. When he received a visa, he was able to escape to Cuba where he lived until the end of World War II. A German officer, who kept placing her name at the bottom on the lists, saved the oldest sister from being deported. With a fake passport she was able to flee to Switzerland. The youngest sister followed her husband to Switzerland, but when he was unable to get a job they sent their children to England whereas they moved to the Netherlands. The children were reunited with their parents in England only to be separated from them again when placed in a camp on the Isle of Man. They were allowed to return to England after a year and they stayed there until the war was over. My grandfather came to Denmark with his family in 1937, hoping to be able to immigrate to Argentina after six months of employment at a company in Copenhagen. However, with limited immigration possibilities in Argentina the family stayed in Denmark. My grandfather’s work permit was renewed time and again with the help of his company, but the family lived in constant fear of being expelled. They fled to Sweden in October 1943 when Germans had planned to arrest and deport Danish Jews. In Stockholm, they moved into a newly built apartment. The family returned to Copenhagen after the war, and in 1952 they were granted Danish citizenship. The story of my family provides me with inspiration, motivation and will to succeed every day. It gives me energy and it makes me want to use my musical abilities to work for peace and tolerance in the world.